Paint -- tests for chemical, physical, and optical properties; appearance - Materials, American Society for Testing & ([S.l.] : ASTM, 2009)
This volume features the latest test methods for the chemical analysis of paints and paint materials, including determination of volatiles, nonvolatiles, pigments, water content, and other constituents.